Perancangan dan Pengujian Performansi Kondensor Tiga Tingkat Pada Alat Pirolisis Plastik - Hanur, Hanur; Dwi Saputra, Gusti Made; Sudia, Budiman; Sisworo, Raden Rinova (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2024)
Plastic is now a very important material and is widely used in modern life, but plastic processing is still a problem because the amount continues to increase, and pyrolysis is one solution. This research aims to design and test the performance of a three-level condenser on a plastic pyrolysis device and determine the results of the products produced.To find out the pyrolysis product from this design, a test was carried out, namely by heating the material (polypropylene/PP type plastic) in the design tool to a temperature of 450℃ and taking the data obtained after carrying out experiments on the design tool.Research shows that this three-condenser plastic pyrolysis device is effective in converting plastic into oil, with the best performance on larger plastic masses. The resulting oil has varying physical characteristics but is generally flammable at high temperatures, although it produces thick smoke and a strong odor.